The Visual Media-Assisted Problem-Based Learning Model: Does It Affect Students' Mathematical Critical Thinking Skills? - Febria Ningsih; Wiwin Handayani; Selvia Erita (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
This study aims to determine the effect of the Problem-Based Learning model assisted by visual media on student learning outcomes on a Similarity topic. This research is experimental research using a randomized pretest-posttest control group design. The population used in this study were ninth-grade students of one of the junior high schools in Kerinci, Jambi. The sample selection used a random sampling technique. Research data was obtained through pretest and posttest. The results showed an effect of the Problem-Based Learning model assisted by the visual media on student learning outcomes on Similarity topics at the 95% confidence level.